A Wearable Hydration Sensor with Conformal Nanowire Electrodes. Issue 6 (27th January 2017) - Yao, Shanshan; Myers, Amanda; Malhotra, Abhishek; Lin, Feiyan; Bozkurt, Alper; Muth, John F.; Zhu, Yong
Abstract : A wearable skin hydration sensor in the form of a capacitor is demonstrated based on skin impedance measurement. The capacitor consists of two interdigitated or parallel electrodes that are made of silver nanowires (AgNWs) in a polydimethylsiloxane (PDMS) matrix. The flexible and stretchable nature of the AgNW/PDMS electrode allows conformal contact to the skin. The hydration sensor is insensitive to the external humidity change and is calibrated against a commercial skin hydration system on an artificial skin over a wide hydration range. The hydration sensor is packaged into a flexible wristband, together with a network analyzer chip, a button cell battery, and an ultralow power microprocessor with Bluetooth. In addition, a chest patch consisting of a strain sensor, three electrocardiography electrodes, and a skin hydration sensor is developed for multimodal sensing. The wearable wristband and chest patch may be used for low‐cost, wireless, and continuous monitoring of skin hydration and other health parameters. Abstract : Wearable skin hydration sensors made of silver nanowires in a rubber matrix are developed based on skin impedance measurement. A flexible wristband for skin hydration sensing and a stretchable multifunctional chest patch for concurrent strain, electrophysiological, and skin hydration sensing are demonstrated for low‐cost, wireless, and continuous health monitoring applications.